(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd bjS Hf GdNWje GdCfUGQj(B: (3KCQJ YOjG hGdNWje ade CVY hUjI CTjGN LYdJ ERGAgG s
(3BNQgG (B:s
(3aCHYOg GdEdg hdG jMji hdG jTai ef GdeQV GdTaGjG s
(3fSNI SGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B273 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B691s
Keywords: (3GdCOHs